Metodologi Penafsiran Al-Qur'an Kontemporer: - Hasani Ahmad Said (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
One of the causes for stagnation of thought experienced by Muslim society at the present time is the difficulty faced in the ongoing dialogue between the reality of religious texts and the reality of contemporary life. This is the reason present-day Muslim scholars are more deeply reflecting on the works of classical Muslim scholars inherited from the at-turāṡ. At the same time in the Western world there has emerged a method, known as hermeneutics, used for understanding scriptural texts. This theoretical approach has attracted much interest from contemporary Muslim scholars who are seeking to apply its method to understanding Islamic classical works (at-turāṡ). The article introduces two figures, namely Nasr Hamid Abu Zayd and Muhammed Arkoun, who having attracted much attention from scholars